MANAJEMEN RISIKO & GOOD CORPORATE GOVERNANCE (GCG) TERHADAP KINERJA KEUANGAN BANK UMUM KONVENSIONAL (Studi Pada Bank BUMN Tahun 2016-2020) - Jihan Karsa Alim Maghribi; Suryakusuma Kholid Hidayatullah (Jurnal AKTUAL, 2022)
The failure of a bank’s performance will affect the trust of customers who have invested capital in the bank. Therefore, it is necessary to apply risk management and good corporate governance to anticipate the occurrence of such performance failures. The study aims to see how risk management and good corporate governance affect financial performance conventional general banks bumn for the 2016-2020 period. The sampling technique chosen was purposive sampling method using secondary data in the form of annual reports from the official website each bank. The data analysis method used in this study is the Classical Assumption Test, Multiple Linear Regression Analysis, and Model Feasibility Test (Goodness of Fit Model) using the SPSS 25 application. The results of this study indicate that non performing loan (npl) variables have a negative effect on financial performance bank. Loan to deposit ratio (ldr) variables have a positive effect to financial performance bank. And self assessment good corporate governance (gcg) variables have a positive effect to financial performance bank bumn. Keywords: Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Self Assessment Good Corporate Governance (GCG) and  Return On Asset (ROA).